Review of Research on and Implementation of Recycled Concrete Aggregate in the GCC - Akmal S. Abdelfatah; Sami W. Tabsh (Advances in Civil Engineering)
The goal of sustainable construction is to reduce the environmental impact of a constructed facility over its lifetime. Concrete is the main material used in construction in the Gulf Cooperation Council (GCC). Therefore, it makes economic and environmental sense to use recycled materials in the making of new concrete for different applications. The objectives of this study are to summarize published research on the use of recycled concrete aggregates in new concrete mixes and examine its implementation in construction and industry in the GCC region. The study showed that while there is reasonable research on recycled concrete, the practical implementation in the region greatly lacks behind, especially due to the lack of economic viability and awareness of such applications at the current time.